Pengembangan Media Pembelajaran Vidioscribe untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPS di SMP Negeri 2 Hu’u - Sumiyati Sumiyati; Husnul Khatimah; Pupu Insaniah; Nurhayati Nurhayati; Fijriani Fijriani (Indonesian Journal of Social Science Education (IJSSE), 2024)
The development of information and communication technology makes it easier for us to access everything, for this we need the competence of each person in mastering various science and technology (IPTEK). As educators, teachers must be able to develop themselves in developing the learning media used in class. The aim of this research is to test the validity, practicality and effectiveness of videoscribe media on the learning outcomes of class VII students at SMP Negeri 2 Hu'u. Researchers developed videoscribe learning media to help students study social sciences (IPS). This type of research uses Research and Development, using the ADDIE model. The sample in this study was 36 class VII students at SMP Negeri 2 Hu'u. The data collection instruments used were interviews, questionnaires and tests. The data analysis techniques used are media validity analysis, media practicality analysis, and media effectiveness analysis. The research results showed that the validity of the media and material was 86% in the "very valid" category. Meanwhile, the practicality of videoscribe media received a percentage of 85% in the Very practical category. Student learning test scores are obtained from pretest results with a Classical Completeness score of 65%. From the results of the pretest, there were 13 students who completed it and 23 students who did not meet the Maximum Completeness Criteria (KKM) with a percentage of 34%. After the posttest was carried out, there were 31 students who completed it and 4 students who did not meet the Maximum Completeness Criteria (KKM), resulting in a percentage of 88%. Thus, it can be said that the use of Videoscribe media in social studies learning at SMP Negeri 2 Hu'u is effective in improving student learning outcomes. This can be seen from the significant increase in student learning outcomes, where initially only 65% of students achieved complete KKM, after the media was implemented. Videoscribe in learning the student's completeness score is 88%.